Effect of short-chain fatty acids on the formation of amylose microparticles by amylosucrase. (20th October 2016) - Lim, Min-Cheol; Park, Kyu-Hwan; Choi, Jong-Hyun; Lee, Da-Hee; Letona, Carlos Andres Morales; Baik, Moo-Yeol; Park, Cheon-Seok; Kim, Young-Rok
Highlights: Effect of fatty acids on the synthesis of amylose microparticles was investigated. Short-chain fatty acids significantly increased production yield of microparticles. The carboxyl group of the fatty acid was found to be responsible for this effect. Fatty acids were ejected from the microparticles at the end of the self-assembly. Physicochemical properties of the microparticles were unaffected by the fatty acids. Abstract: Amylose microparticles can be produced by self-assembly of amylose molecules through an amylosucrase-mediated synthesis. Here we investigated the role of short-chain fatty acids in the formation of amylose microparticles and the fate of these fatty acids at the end of the reaction. The rate of self-assembly and production yields of amylose microparticles were significantly enhanced in the presence of fatty acids. The effect was dependent on the length of the fatty acid carbon tail; butanoic acid (C4) was the most effective, followed by hexanoic acid (C6) and octanoic acid (C8). The amylose microparticles were investigated by carrying out SEM, XRD, Raman, NMR, FT-IR and DSC analysis. The size, morphology and crystal structure of the resulting amylose microparticles were comparable with those of amylose microparticles produced without fatty acids. The results indicated the carboxyl group of the fatty acid to be responsible for promoting the self-assembly of amylose chains to form microparticles. The fatty acids were eventually removed from the microstructure through the tight association of amylose double helices to form the amylose microparticles.